Peer Tutoring through an Ecoprint Project in Arts and Culture Learning at Madrasah Ibtidaiyah - Alfian Eko Widodo Adi Prasetyo; Eny Kusumastuti; Zuraidah Abdullah; Fitri Yuliawati (Universitas Islam Negeri (UIN) Salatiga, 2026)
Objectives: This research aims to test the effectiveness of peer tutoring through an ecoprint project to improving learning outcomes in arts and culture learning at Madrasah Ibtidaiyah (Islamic primary school) students. Method: The research employed a quantitative experimental design using a one-group pretest-posttest method. The sample comprised 47 students at Madrasah Ibtidaiyah. Data collection was carried out through structured peer tutor observations and performance-based assessment tests measuring students’ craft-making abilities. The collected data were analyzed using a Paired Sample T-Test and N-Gain calculations to determine the statistical significance and instructional impact. Results: The results of the Paired Sample T-Test showed a significance value of 0.000 (p < 0.05), which indicated a statistically significant difference in students' project-making skills after peer tutor intervention, but the N-Gain score of 0.1717 (17.17%) indicated that the level of effectiveness of the peer tutor method was relatively low. Theoretical Contribution: This research found five steps to implementing peer tutoring through ecoprint projects in arts and culture learning. Hands-on mentoring and structured group presentations within an arts-based curriculum represent a new finding. The results of this research reinforce Islamic educational theory that emphasizes ta'awun (cooperation) and character building through practical engagement, and demonstrate the importance of designing appropriate peer tutoring methods in arts and crafts subjects. Implication: Peer tutoring in arts and culture learning can be implemented through five stages by taking into account adequate student readiness, balanced group composition, and active teacher guidance.